Measurement model of empowerment for women and girls using social media - Abdul Hamid, Norsiah (Universiti Kebangsaan Malaysia, 2015)
The trend in social media usage among a group at risk in Malaysia, particularly women and girls has shown a significant increase in few years back.The utilization of social media by this group has created benefits that should be taken into consideration, which relates to empowerment. Studies on social media benefits to women and girls find that these tools can help the group to improve their life status, particularly in entrepreneurship, knowledge and skills enhancement, and economic and career improvement. This article discusses findings from a research conducted in Malaysia on social media as an empowerment tool which focuses on five important dimensions namely economy, social and cultural, legal, political, and psychology.The study employed a survey that uses a set of printed questionnaire distributed to women and girls who use social networking sites, particularly Facebook. Using a sample of 88 responses in an exploratory study, the researchers developed a 5-factor 24-item instrument to measure empowerment comprising of the five hypothesized dimensions.A second-order model of empowerment was also proposed as a measure of overall social media empowerment.Results confirm factor structures of the empowerment model and suggest a more parsimonious instrument for each; a 5-factor 14-item scale for social media empowerment. Goodness-of-fit indices for putative models of factor structures and the second-order model are presented.The result shows that the five dimensions are significant to the empowerment model of women and girls.The findings can contribute greatly to a better understanding of the empowerment mechanism behind social media issue pertaining to women and girls.